SPECIFIC DIRECTIONS FOR RECOGNITION, MEASUREMENT AND DISCLOSURE OF LIABILITIES IN THE ICT SECTOR (International Congress on Economics, Management and Business Studies, 2026)
The article examines contemporary methodological problems of liability recognition, measurement and disclosure in financial statements at enterprises in the field of information and communication technologies (ICT). The author identifies three main methodological problems - the uncertainty of the criteria for recognizing liabilities, the incorrect application of measurement methods and incomplete disclosure. For each problem, directions for solutions are proposed and their practical effectiveness is substantiated on the example of Uzbektelecom JSC.
Keywords: recognition, measurement, disclosure, methodological issues, IFRS 37, ICT sector, financial reporting.